Establishing the Diagnostic Reference Levels for Common Dubai Health Adult Nuclear Medicine Examinations - Entesar Z. Dalah; Najlaa K. Al Mazrouei; Zahra A. Al Ali (Life)
Nuclear medicine (NM) procedures are performed using unsealed radioactive sources that are administered to patients, resulting in both internal and external exposure for patients and staff alike. Optimization is mainly concerned with ensuring the use of the lowest sufficient level of radiation to perform a procedure while maintaining adequate image quality. Diagnostic reference levels (DRLs) have been proven effective in aiding optimization in clinical practice. This dose review aims to establish an inclusive DRL system for the common adult NM procedures performed at Dubai Health. Our defined DRLs will focus on both the administered radiopharmaceuticals and the radiation dose metrics derived from hybrid computed tomography (CT). Dose surveys for 1439 adult nuclear medicine procedures performed over twelve months were collected and retrospectively analyzed. DRLs were obtained for a total of eight scintigraphy procedures, four hybrid positron emission tomography procedures with CT (denoted PET/CT), and five target sites for CT hybrid single-photon emission tomography with CT (denoted as SPECT/CT). Our derived DRLs for the scintigraphy, hybrid SPECT/CT and PET/CT procedures are within the reported national DRLs, except for the CT dose of the hybrid SPECT/CT for the neck, abdomen and chest/abdomen sites and the 18F PSMA administered activity. A fixed activity dose was administered for a scintigraphy procedure that is weight dependent. This patient dose review serves as a foundational effort aiming to optimize radiation safety and standardize diagnostic practices in NM. Further research is needed to enhance adherence to safety benchmarks.